Implementation of Preparation of Financial Reports of MSMEs Based on Financial Accounting Standards for Micro, Small and Medium Entities (SAK-EMKM) Case Study at CV Hubol's - Adventus Lumban Siantar; Dwi Saraswati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The topic of this research is